DINAMIKA KERJASAMA INDONESIA DAN MALAYSIA TENTANG PENEMPATAN DAN PERLINDUNGAN TENAGA KERJA - Dwi Wahyu Handayani; Agus Hadiawan; Aman Toto Dwijono (Jurusan Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2015)
The research problem is how the dynamics of cooperation between Indonesia and Malaysia on the placement and protection of labor? The results of the study with qualitative descriptive method is to answer how the dynamics of cooperation between Indonesia and Malaysia on the placement and protection of labor. Usefulness theoretically is enriching contemporary studies in the field of government and international relations. Practical usefulness, can provide useful information for the government as the frontline public services. Bilateral relations between Indonesia and Malaysia regarding labor can not be separated from each destination to fulfill the realization of national interests. The results of the study is the first, migrant workers in Malaysia is a rational economic phenomenon which is based interests of the two countries, the demand for high-Malaysia on migrant workers, Indonesia also benefit the economy as the biggest source of foreign exchange and help the national economy. Secondly, the dynamics of cooperation efforts the placement and the protection of migrant workers in Malaysia from time to time is influenced by 2 states internal constraints that the employment system of each country. Malaysia and Indonesia has not ratified the Migrant Workers Convention. Malaysia did not have laws that specifically deal with the informal sector workers. Malaysia is also opposed to the concept of legally binding and illegal migrant worker protection standards based on human rights. Third, Indonesia bargaining power is weak because of the bad image of workforce management that will work overseas, including the presence of illegal workers, migrant workers without the expertise and understanding of the culture of the recipient country, unclear contract of employment, the existence of extortion against migrant workers in the country.